A study case on the impacts of tourism sector towards economic growth in Melaka / Aisyah Othman - Othman, Aisyah (Faculty of Business and Management, 2010)
This study is to understand the economic structure and interdependencies of different sectors of the economy. Economic studies stressed on GDP, CPI and GDI for tear 2000 to 2009, will discover better understand the size and structure of the tourism industry in a given region and its linkages to other sectors of the economy. Such understandings are helpful in identifying potential partners for the tourism industry as well as in targeting industries as part of regional economic development strategies. Issues such as economic growth, stability, and seasonality may be addressed as part of this study. The focus of this study will be based on the Melaka tourism growth and economic growth. The principal methods here are visitor spending surveys, analysis of secondary data from government economic statistics, economic base models, input output models and multipliers. Thus, tourism sectors significant relationship to the economic growth and development. As guidance to the past research that have been done, this study will examine the relationship between economic growth and tourism sector.